EFEKTIVITAS PENERAPAN MODEL GUIDED DISCOVERY PADA POKOK BAHASAN KLASIFIKASI HE WAN TERHAPAP HASIL BELAJAR BIOLOGI DITINJAU DARI MOTIVASI BELAJAR SISWA KELAS X SMA NEGERI 3 JAYAPURA TAHUN PELAJARAN 2012/2013 - Sibarani, Binsar; Simbiak, Maikel (Jurnal Ilmu Pendidikan Indonesia, 2014)
This study aimed to determine : (1) distinction of students biology learning outcomes who follwed guided discovery learning model with direct instructional (conventional) (2) The diffrences of students learning outcomes in bilogy who has higher motivation, medium, and poor in learning, (3) There is interaction of learning model with motivation level on bilogy class. From 3 (three) propoded hipotesis the results showed that (1) there is significantly diffrenent between guided discovery learning model with drect intrucstional model, value sig 0,001 < Î± 0,05. (2) there is significant interaction between level of students motivation in learning biology learning outcome, value sig 0,002 < Î± 0,05, and (3) there is no interaction between the model of learning with the students level of motivation, value sig 0,611 > Î± 0,05. Keywords: Guided Discovery Learning, Direct Instructional, Motivation to Learn, and Learning Outcomes.